Assessing Biometric Predictors of Gestational Age Among Ghanaian Women: The Quadratic Classifier Approach - Abukari Alhassan (European Scientific Journal, ESJ, 2025)
Aims/Objectives: Research has revealed that some illnesses, such as gestational diabetes, might affect a woman's gestation differently. Not all pregnant women who are diagnosed of gestational diabetes, experience gestational variations. Therefore, studying other factors influencing gestational variations amongst women is essential. Subject/Methods: The biostatistics department at the War Memorial Hospital in Navrongo, the capital of the Kasena-Nankana municipality in Ghana's Upper East, provided the study's data. It includes information on women and the children who were born to them between January 2014 and January 2017 with a sample size of 1085. The study examined the impact of some characteristics of women on their gestational variation using a quadratic discriminant analysis. Results: The main factors influencing the separation of women into different gestational stages in the Municipality are parity, age, and the weight of the unborn child. Conclusion: However, the study found that parity was the most important factor in classifying women into below Estimated Date of Confinement, within Estimated Date of Confinement, and above Estimated Date of Confinement of gestation.